Deconstructing the trypanosome cytoskeleton: from structures to functions via components and complexes. - Portman, N (2011)
Trypanosomatid protozoan parasites are the causative agents of a number of diseases responsible for the death of thousands of people in developing countries. There is currently little hope for the development of vaccines and existing treatment regimens are associated with high toxicity. Trypanosoma brucei is the etiological agent of devastating parasitic disease in humans and livestock in sub-saharan Africa. The pathogenicity and growth of these parasites are intimately linked to their shape and form which are in turn derived from a highly ordered microtubule-based cytoskeleton. Here I have investigated some of the critical structures of the cytoskeleton in terms of their molecular composition with a view toward interrogating their functions. I have used a combined reverse genetics/comparative proteomics approach to identify over 20 novel components of the paraflagellar rod, an essential structure for the mammalian infective form of the parasite. I have iterated this approach to define interdependent sub-groups within the cohort which provide clues to the function of the paraflagellar rod. I next applied the same comparative proteomics techniques to investigate the differences between the protein composition of two life-cycle stages of the parasite. I have identified novel components of a unique mobile transmembrane junction called the flagella connector, and of the flagellum attachment zone, a structure that is essential for cell division. In addition I have defined a pair of paralogous cytoskeletal proteins that show life-cycle stage specificity. Finally, I have used electron tomography, reverse genetics and in situ protein tagging to define the morphology of the flagellar pocket collar, a critical structure required for parasite viability, and provide new insights into its molecular composition, function and biogenesis.